2022
DOI: 10.1186/s12938-022-01032-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evaluation of the Stemoscope electronic tele-auscultation system

Abstract: Background With the spread of COVID-19, telemedicine has played an important role, but tele-auscultation is still unavailable in most countries. This study introduces and tests a tele-auscultation system (Stemoscope) and compares the concordance of the Stemoscope with the traditional stethoscope in the evaluation of heart murmurs. Methods A total of 57 patients with murmurs were recruited, and echocardiographs were performed. Three cardiologists we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The development of such algorithms will assist the veterinary profession on a global scale and aid in creating algorithms for other species. This will ultimately result in increased telemedicine capabilities to assist rural, remote and even third-world veterinarians [13,44]. Adding recordings to a patient's electronic medical record also helps to document future disease progression [13].…”
Section: Discussionmentioning
confidence: 99%
“…The development of such algorithms will assist the veterinary profession on a global scale and aid in creating algorithms for other species. This will ultimately result in increased telemedicine capabilities to assist rural, remote and even third-world veterinarians [13,44]. Adding recordings to a patient's electronic medical record also helps to document future disease progression [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a small, portable device for auscultation called the Stemoscope (Hulu Devices, California, USA) was developed. Fan et al [32] evaluated this and concluded that in-person auscultation and tele-auscultation by the Stemoscope were in agreement with manual acoustic auscultation and that the Stemoscope can be used in telemedicine.…”
Section: Auscultationmentioning
confidence: 91%
“…Remote auscultation, particularly through electronic stethoscope systems, plays a critical role in telemedical physical examinations. 8 14 Our previous study found that conventional auscultation was superior to that of real-time remote cardiac auscultation. 13 Thus, an appropriate support system is required to improve remote cardiac auscultation.…”
Section: Introductionmentioning
confidence: 99%